Waxy Gene Factor and Residual Protein of Rice Starch Granules - Villareal, C.P.; Juliano, Bienvenido O. (Wiley, 1986)
Residual protein of rice starch granules prepared from milled rice by protein extraction with sodium dodecylbenzene sulfonate or alkaline protease treatment was related to amylose content. SDS‐polyacrylamide disc gel electrophoresis confirmed that the major protein in nonwaxy starch granules was the Wx gene product with subunit molecular weight of about 60,000 daltons. The Wx gene product was absent in waxy starch granules.